Incidence of ankle contracture after moderate to severe acquired brain injury - Singer, B.; Gnanaletchumy, J.; Singer, K.; Allison, Garry; Dunne, J. (Elsevier, 2004)
Objective. To examine an adult population undergoing rehabilitation after brain injury to determine the incidence of ankle contracture and factors contributing to the development of this deformity. Design. Descriptive study. Setting. Specialist inpatient neurosurgical rehabilitation unit in Australia. Participants. Patients (N=105) admitted with a new diagnosis of moderate to severe brain injury over a 12-month period. Interventions. Not applicable.Main outcome measures. Maximal ankle dorsiflexion range and the presence of abnormal muscle tone affecting the lower limb(s) were evaluated at weekly intervals. Ankle contracture was defined as maximal passive range of less than 0 dorsiflexion with the knee in extension. Patients were grouped into 3 muscle tone categories: normal, predominantly spastic, or predominantly dystonic. Age, sex, mechanism and severity of brain injury, time to onset of ankle contracture, total length of hospital stay, and discharge mobility status data were also recorded.Results. Muscle tone was designated as normal in 68 (64.7%), as spastic in 14 (13.3%), and as dystonic in 23 (21.9%) patients. The incidence of ankle contracture was 16.2% (17/105 cases). Ankle deformity correlated closely with muscle tone category. Of 23 cases with dystonic muscle overactivity, 17 developed contracture at some point between 1 and 16 weeks after brain injury, although no subject with normal tone or spasticity developed the deformity. There was a weak association between the severity of brain injury and development of ankle contracture. Conclusions. The incidence of ankle contracture was much lower than previously reported. Dystonic overactivity of the plantarflexor and invertor muscles is a major predisposing factor to ankle contracture.